2022
DOI: 10.3389/fnmol.2022.932075
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of serum alkaline phosphatase and globulin levels in patients undergoing intravenous thrombolysis

Abstract: BackgroundIn previous studies, alkaline phosphatase (ALP) level was a prognostic factor for patients with ischemic stroke, and globulin level was associated with hemorrhagic transformation (HT) after intravenous thrombolysis (IVT). However, the association between these serum biomarkers and prognosis in patients with acute ischemic stroke (AIS) who undergo IVT remains unclear. This study aimed to investigate the characteristics of serum ALP and globulin levels after IVT and to assess the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Furthermore, Zhong et al ( 22 ) observed similar results in their study of 2,944 enrolled AIS patients. We also performed an analysis of poor functional outcomes, and similar to Zhu et al and Kim et al, we found that higher ALP levels were associated with an increased risk of poor functional outcomes ( 11 , 19 ). However, Guo et al and Liu et al found that elevated ALP levels were not associated with poor functional outcomes in stroke patients ( 18 , 20 ).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, Zhong et al ( 22 ) observed similar results in their study of 2,944 enrolled AIS patients. We also performed an analysis of poor functional outcomes, and similar to Zhu et al and Kim et al, we found that higher ALP levels were associated with an increased risk of poor functional outcomes ( 11 , 19 ). However, Guo et al and Liu et al found that elevated ALP levels were not associated with poor functional outcomes in stroke patients ( 18 , 20 ).…”
Section: Discussionsupporting
confidence: 74%
“…Inhibition of ALP has been shown to prevent the formation of vascular atherosclerosis ( 8 ). Traditionally recognized as a marker for skeletal or hepatobiliary dysfunction ( 9 , 10 ), ALP is now considered indicative of atherosclerosis and inflammatory responses ( 6 , 11 ). Studies have indicated that elevated serum ALP levels are linked to increased atherosclerosis in coronary and peripheral arteries and that higher ALP levels are independently associated with the risk of cardiovascular disease (CVD) and mortality events ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, an ideal stroke biomarker should be capable of predicting stroke prognosis and facilitating therapeutic stratification and monitoring ( 5 ), for example by indicating risk of hemorrhagic transformation after stroke or after tissue type plasminogen activator treatment (rt-PA). In fact, Zhu et al ( 25 ) already demonstrated that higher serum ALP levels were independently associated with a poor outcome in patients after intravenous thrombolysis.…”
Section: Discussionmentioning
confidence: 99%